SOSIALISASI PEMANFAATAN MINYAK JELANTAH PADA MASYARAKAT DESA MULYASARI BAYONGBONG - Fatimah, Dini Destiani Siti; Wijaya, Muhammad Raffly; Raniyanti, Ulpah; Rabbani, Muflih Rafi; Yudistira, Restu; Fhayed, Nazwan Hanif Al; Dwiyanti, Karinna Nur; Nazrulloh, Ilham; Aditia, Angga; Zulkarnaen, Eggi; Firmansyah, Muhamad Riksa; Anggana, Mochamad; Madani, Abdullah Ibnu; Abdusyukur, Muhamad; Nuraisah, Nuraisah; Melinda, Susan; Sriayuwahyuni, Putri; Parlina, Rina; Zaky, Ahmad Sulthan; Pratiwi, Revina Zulianti; Malik, Jalaludin (Jurnal PkM MIFTEK, 2023)
Mulyasari Village has approximately forty Micro, Small and Medium Units in the food sector, which is an important pillar in the local economy. This is a beneficial situation for society, but has negative consequences for the environment. The thing that is detrimental to the environment from this food processing business is that a lot of used cooking oil is thrown into the environment. This is because used cooking oil as a by-product is considered useless so it is thrown away by the community. In an effort to solve this problem, it is necessary to find a breakthrough in the management of used cooking oil so that it can be used as a product with economic value. The aim of the service is to provide outreach to the people of Mulyasari Village, Bayongbong District to recycle used cooking oil waste into aromatherapy candles. Therefore, Group 19 of the Garut Institute of Technology Real Work Lectures, hereinafter referred to as Mtechsquad 19, carried out the socialization program in several Community Units of Mulyasari Village, Bayongbong District, Garut, door to door and centered on the commemoration of the 78th Anniversary of the Republic of Indonesia. The implementation of this work program has succeeded in getting a positive response from the community.